2013
DOI: 10.1115/1.4024290
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cutting Force Induced Surface Shape Variation in Face Milling Using High-Definition Metrology1

Abstract: igh-definition metrology (HDM) systems withflne lateral resolution are capable of capturing the surface shape on a machined part that is beyond the capability of measurement systems employed in manufacturing plants today. Such surface shapes can precisely reflect the impact of cutting processes on surface quality. Understanding the cutting processes and the resultant surface shape is vital to high-precision machining process monitoring and control. This paper presents modeling and experiments of a face milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…First, model f ðU l ðsÞ; b l Þ is employed to capture the relationship between the process inputs and the surface height in face milling processes. It is reported that the surface height variation in a face milling process is strongly influenced by a number of engineering factors [13,20,21], including (1) the product/surface design that characterizes the design patterns of a surface, e.g., size, shape, and spatial distribution of holes and slots, (2) physical attributes of part materials, such as the defects and heterogeneous physical attributes caused by manufacturing flaws from suppliers, (3) manufacturing process conditions, such as feed rate, spindle tilt, spindle speed, depth of cut, cutter path, and clamping force, and (4) multistage interdependence that characterizes the effects of downstream stages on the surface shapes created in the upstream stages. For details, please refer to Ref.…”
Section: Engineering-guided Multitask Learning Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…First, model f ðU l ðsÞ; b l Þ is employed to capture the relationship between the process inputs and the surface height in face milling processes. It is reported that the surface height variation in a face milling process is strongly influenced by a number of engineering factors [13,20,21], including (1) the product/surface design that characterizes the design patterns of a surface, e.g., size, shape, and spatial distribution of holes and slots, (2) physical attributes of part materials, such as the defects and heterogeneous physical attributes caused by manufacturing flaws from suppliers, (3) manufacturing process conditions, such as feed rate, spindle tilt, spindle speed, depth of cut, cutter path, and clamping force, and (4) multistage interdependence that characterizes the effects of downstream stages on the surface shapes created in the upstream stages. For details, please refer to Ref.…”
Section: Engineering-guided Multitask Learning Surfacementioning
confidence: 99%
“…The functional form of f ðÁÞ should be determined based on a thorough understanding of the process physics. For instance, in a face milling process, the global trend can be approximated by a linear term [20,13], i.e., f ðUðsÞ; bÞ ¼ ½I; MRRðsÞb, where I is a column vector of ones, MRR(s) is a column vector and represents the material removal rate (MRR) at location s, and b ¼ ½b 0 ; b 1 T is a 2  1 vector. This linear representation reveals the fact that higher axial cutting force variations due to MMR variation may result in large displacement between the surface and the cutter, causing significant surface height variations.…”
Section: Engineering-guided Multitask Learning Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of hard machining over grinding are high flexibility, possible complete machining, less ecological burden, and higher productivity Material Removal Rate (MRR) [2], However, its industrial potential is still limited due to unsatis factory surface integrity and the attainable dimensional and shape accuracy [3,4]. Special interest is focused on precision and highprecision hard turning (PHT) operations which demand the Rz roughness parameter to be at 2.5^4 pm and below 1 pm, respec tively [5][6][7]. Moreover, it is important to investigate the capability profiles of both these operations to the functionality of the machined surfaces [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Surface form is predominantly considered as one of the most important features of practical product surfaces due to its crucial influence on the functional behavior of a machined part [1][2][3][4][5][6][7][8]. The form error estimation under various machining conditions is an essential step in the assessment of part surface quality generated in machining processes [9].…”
Section: Introductionmentioning
confidence: 99%